Mediation of Self-Discipline on the Effect of Fiqh Learning and Social Support on the Implementation of Fardhu Prayers - Nazha Novi Prihastuti; Rihab Wit Daryono (JIE (Journal of Islamic Education), 2024)
This research highlights the social conditions that influence the intensity of the performance of fardhu prayers. Students with solid discipline tend to maintain their observance of fardhu prayers better. This research aims to determine the role of self-discipline in mediating the influence of fiqh learning and social support on the intensity of students' implementation of fardhu prayers. This research uses a quantitative approach with survey research methods. The research method uses probability with random sampling techniques, with a sample size of 78 students. The research was conducted at MTsN 12 Madiun. The data analysis technique uses PLS-SEM to test the conceptual model. The research results show that learning fiqh significantly influences the intensity of performing fardhu prayers, as evidenced by the β-value = 0.296 and the ρ-value = (<0.05) 0.015. Fiqh learning has a significant positive effect on self-discipline as evidenced by β-value = 0.328 and ρ-value = (<0.05) 0.001. Self-discipline has an insignificant positive impact on the intensity of performing fardhu prayers. the β-valueis 0.207 and the ρ-value = (<0.05) is 0.089. Social conditions have an insignificant positive influence on the intensity of independent fardhu prayers as evidenced by a β-value = 0.211 and ρ-value= (<0.05) 0.119. Social conditions significantly influence self-discipline as evidenced by β-Values ​​​​= 0.459 and ρ-Values= ​​(<0.05) 0.000.